Evaluasi Unjuk Kerja Peralatan Pada Kegiatan Penambangan Pit-3 Timur, PT. Bukit Asam Tbk - Dwi T. S. Fambudi,; Harjuni Hasan,; Henny Magdalena,; Revia Oktaviani,; Agus Winarno, (ReTII, 2023)
Bukit Asam Tbk is a company operating in the coal mining sector located in Lawang Kidul District, Muara Enim Regency, South Sumatra Province. Observations were carried out on mining activities at Pit-3 Timur and coal handling operational unit-5 to find out what obstacles existed during production activities such as machine breakdowns, queues for transportation equipment, and so on. Therefore, it is necessary to carry out routine maintenance and monitoring of equipment, so that existing obstacles can be minimized. The actual total production value on the mining front is 207,719.15 tons, with the effectiveness of the digging-loading tool being 63.52% and the effectiveness of the tool being 64.89%.